New species of Blakea (Melastomataceae: Pyxidantheae) from Costa Rica and Panama - Almeda, Frank; Solano, Daniel; Penneys, Darin S.; Kriebel, Ricardo (Phytotaxa, 2026)
Blakea barbellata and B. loboana from Panama and Costa Rica respectively, are described, illustrated, mapped, and compared with morphologically similar species. Blakea barbellata is readily distinguished by its indumentum of barbellate trichomes, solitary flowers in upper leaf axils, uppermost nodes densely covered with and concealed by appressed ± flattened straw-colored trichomes; free outer and inner floral bracts of differing shapes and sizes; laterally coherent anther thecae, and dorso-basal triangular deflexed rugose appendages 1.5 mm long. Blakea loboana can be recognized by its floral peduncles 4–8 mm long, flowers mostly paired in upper leaf axils, elliptic-lanceolate to lanceolate floral bracts (the outer of which are longer than the inner ones), linear-oblong calyx lobes that equal or exceed petal length in bud, bluntly retuse petals, and ovary apex beset with gland-tipped white trichomes 3 mm long. Based on IUCN Red List Categories and Criteria, a conservation assessment of Data Deficient and Vulnerable are recommended for Blakea barbellata and B. loboana, respectively.